Historical, tactical and structural analysis of the 4:2 defensive play system in handball - Espina, J. J. (Journal of Human Sport & Exercise, 2013)
This study aims to show how the 4-2 Defensive Play System in Handball has developed both tactically and structurally over time. Logically, since its first appearance in Czechoslovakia during the 1960s, there have been certain physical, technical and tactical changes. The System has also evolved to be used both in Grassroots Sport (from Junior to Youth) and in situations of numerical superiority. The study begins with a number of diagrams that make it easier to understand the most significant tactical aspects involved.